1997
DOI: 10.1016/s0197-4580(97)00150-4
|View full text |Cite
|
Sign up to set email alerts
|

Age and Experience-Dependent Representational Reorganization During Spatial Learning

Abstract: Age and experience-dependent representational reorganization during spatial learning NEUROBIOL AGING 18(6) 651-659, 1997.-Previously, we found that aged rats showed a significant enhancement of hippocampal CA1 place cell spatial specificity, as well as a reduction of hilar place cell spatial specificity, during asymptote performance of a spatial memory task. Because such an age effect was not observed when animals performed a nonspatial task, the present study tested the hypothesis that the different patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Past analyses of hippocampal information processing in aged animals have focused either exclusively on cells of the CA1 subregion Shen et al, 1997;McEchron et al, 2001; or have combined the data obtained from the CA1 and CA3 subregions for analytical purposes Oler and Markus, 2000;Wilson et al, 2003Wilson et al, , 2004Wilson et al, , 2005. In studies of aging that did analyze subregions separately (Mizumori et al, 1996;Mizumori and Kalyani, 1997), the experimental conditions for recordings were not suitable for detecting the distinctive features of CA1 and CA3 encoding in response to changes in the environment. In making this hippocampal subregion comparison, we found that the CA1 cells of aged rats had firing properties similar to those of the young adults: both groups had overall firing rates at similar values and made some adjustments in firing rates in response to a change in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Past analyses of hippocampal information processing in aged animals have focused either exclusively on cells of the CA1 subregion Shen et al, 1997;McEchron et al, 2001; or have combined the data obtained from the CA1 and CA3 subregions for analytical purposes Oler and Markus, 2000;Wilson et al, 2003Wilson et al, , 2004Wilson et al, , 2005. In studies of aging that did analyze subregions separately (Mizumori et al, 1996;Mizumori and Kalyani, 1997), the experimental conditions for recordings were not suitable for detecting the distinctive features of CA1 and CA3 encoding in response to changes in the environment. In making this hippocampal subregion comparison, we found that the CA1 cells of aged rats had firing properties similar to those of the young adults: both groups had overall firing rates at similar values and made some adjustments in firing rates in response to a change in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, despite a diminished entorhinal input, CA1 and CA3 "place fields" of aged rats with behavioral impairments are not degraded with respect to field size, coherence, and other parameters that characterize spatial information content (Rosenzweig et al 2003;Wilson et al 2003). Instead, alterations in encoding are revealed in the experience-dependent plasticity of those cells, effects that are manifest in distinct settings across different hippocampal subregions Mizumori and Kalyani 1997;Shen et al 1997;Wilson et al 2005).…”
Section: Features Of Neurocognitive Aging In the Function Of Existingmentioning
confidence: 99%
“…Indeed it has been shown that such measures of place fields vary with experience (e.g. Mizumori and Kalyani, 1997;Puryear et al, 2006). Also, the degree of temporal coherence amongst a group of neurons could depend on their recent activation patterns (e.g.…”
Section: Hierarchically Organized Context Processing Within Hippocampusmentioning
confidence: 99%